Altruism or self-interest in tomorrow's veterinarians? A metric conjoint experiment and cluster analysis - Feakes, Adele; Lindsay, Noel; Palmer, Edward; Steffens, Paul (Frontiers in Veterinary Science, 2023)
Introduction Altruism is considered a trait of veterinary and other health professionals, but the level of altruism in the veterinary profession is unknown. We designed a metric conjoint experiment to reveal other-orientation (an individual's caring concern for the wellbeing of others) and self-interest. We draw on the ‘Theory of Other-Orientation’, which states that individuals' decision-making heuristics can be impacted by their other-orientation independent of their self-interest. In patient-focused contexts, highly other-oriented or altruistic (veterinary) professionals may care too much for others and suffer immediate or cumulative financial and personal costs of such caring. At the same time, other-orientation can enhance job-related attitudes and outcomes, such as job satisfaction. Methods In a metric conjoint experiment, Australian final-year veterinary, science, nursing, entrepreneurship, and engineering students rated eight job scenarios with orthogonally arranged high and low levels of three job characteristics (n = 586) to provide observed measures of other-orientation and self-interest. Results A two-way MANOVA showed other-orientation or self-interest differed per discipline, but not gender. Veterinary (and engineering) respondents were less other-oriented than nursing respondents. Veterinary (and entrepreneurship) respondents were more self-interested than nursing respondents. K-Means cluster analysis confirmed four distinct profile groupings—altruistic/self-sacrificing, ‘both other-self’, self-interested and selfish—aligning with the discourse in the literature. Human nursing respondents stood out for the most members (50%) in the ‘both other-self’ profile compared to veterinary respondents (28%). Respondents of one of three veterinary schools stood out for the most members (19%) in the altruistic/self-sacrificing group. Discussion Our metric conjoint experiment illustrates an alternative to ‘self-report’ items with Likert-scaled responses. Our finding of the ‘both other-self’ group adds to the literature, which considers that other-orientation and self-interest are separate constructs that are difficult to co-exist in individuals. This mix of traits is deemed helpful by organizational psychology scholars, for sustainability and wellbeing, especially for healthcare professionals involved in high-frequency and intense, patient-focused interactions. Our findings highlight the need for more research on the potential role of other-orientation and self-interest in veterinary school admissions processes, the hidden or taught curricula, job-related attitudes and beliefs, and wellbeing and professional sustainability in the veterinary sector.